PENGUKURAN TINGKAT PEMAHAMAN MAHASISWA TERHADAP VISI MISI PROGRAM STUDI PENDIDIKAN BIOLOGI FKIP UNTAN - Andri Maulidi; Syamswisna Syamswisna; Entin Daningsih; Eka Ariyati; Reni Marlina (BIO-PEDAGOGI, 2018)
The Implementation of education in Higher Education must have the vision and mission to achieve a certain goal. The result of the vision and mission statement is socialized to get feedback as an evaluation and perfection of the vision and mission. The achievement of vision and mission that have been determined must be known, understood, and implemented by all academicians including students. This research was conducted to measure the level of students' understanding of the vision and mission of Biology Education Study Program of FKIP Untan. This research used qualitative approach with descriptive study. The subjects in this research were 246 students of Biology Education Study Program of FKIP Untan class of 2015, 2016, and 2017. The research instrument used was a questionnaire with closed and open statement. The results of this study indicated that in general the students have understood the vision and mission well. Data analysis showed that 236 (95,93%) students have read vision and mission, 190 (77,24%) and 204 (82,93%) students knew about vision and mission, 203 (33,44%), 101 (64%) students were the highest percentage of students who read the vision and mission in standing banner or class and in academic guidance book. Furthermore, 162 students (65.85 %) agreed that they have been well informed about the vision and mission, 165 students (67.07%) agreed that they have understood the vision and mission, 173 students (70.33%) agreed with the existence of vision and mission, and 159 students (64.63%) agreed that the vision and mission were used as references.